Pleural effusion from intrathoracic migration of a ventriculo-peritoneal shunt catheter: pediatric case report and review of the literature - Federica Porcaro; Emidio Procaccini; Maria Giovanna Paglietti; Alessandra Schiavino; Francesca Petreschi; Renato Cutrera (BMC, 2018)
Abstract Background Pleural effusion is a rare complication of ventriculo-peritoneal (VP) cerebrospinal fluid (CSF) shunting and its diagnosis is difficult in patients with neurological and consciousness impairment. Case report Herein we report the case of a child affected by Pfeiffer syndrome and hydrocephalus, shunted at the age of 3 months, who developed acute respiratory failure due to a right-sided pleural effusion 2 years later. Plain chest radiographs and computed tomography (CT) showed the intrathoracic migration of the right VP shunt abdominal tip. Beta-2 transferrin, a marker for CSF, was found in the pleural fluid and the hypothesis of a CSF hydrothorax was confirmed. Effusion was treated with a thoracentesis. Seven days after, the right VP shunt was revised; a ventriculo-atrial (VA) shunt was also placed on the left side to serve as the main CSF shunt and to prevent the recurrence of hydrothorax. We review the pediatric cases of CSF hydrothorax reported in the literature and discuss the mechanisms underlying this complication together with the possible treatments. Conclusion Pleural effusion due to VP shunt insertion is a rare and potentially life-threatening condition that should be suspected in any patient with a VP shunt and respiratory failure. Signs of hydrothorax may moreover represent the only clinical evidence of a shunt-related complication in case of neurologically severely compromised patients in which neurologic examination cannot help to make a diagnosis.